2021
DOI: 10.1111/jcmm.16430
|View full text |Cite
|
Sign up to set email alerts
|

Galangin suppresses RANKL‐induced osteoclastogenesis via inhibiting MAPK and NF‐κB signalling pathways

Abstract: Osteoporosis is a group of diseases in which the bone mass is significantly reduced, predisposing patients to spontaneous bone fragility and bone fractures. It has been reported that more than 70 million people worldwide are affected by this life-threatening problem. 1 The integrity and structure of the skeleton are precisely regulated by osteoclastogenesis (mediated by osteoclasts) coupled with osteogenesis (mediated by osteoblasts). 2,3 However, excessive bone resorption by osteoclasts destabilizes this bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…However, IL-6 production was not increased in the osteoclast differentiation assay with sRANKL and M-CSF ( Figure 5 b). Previous studies have shown that activation of p38 and ERK phosphorylation in the MAPK signaling pathway, as well as downstream factors of NFATc1, c-Fos, and C-Jun are important [ 37 ]. As GPA suppresses activation of the MAPK, AP-1, and NF-κB signaling pathways in macrophages [ 38 ], alveolar bone resorption may occur in vivo through the indirect action of IL-6 suppression because of its anti-inflammatory effect and its direct effects on BMMCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-6 production was not increased in the osteoclast differentiation assay with sRANKL and M-CSF ( Figure 5 b). Previous studies have shown that activation of p38 and ERK phosphorylation in the MAPK signaling pathway, as well as downstream factors of NFATc1, c-Fos, and C-Jun are important [ 37 ]. As GPA suppresses activation of the MAPK, AP-1, and NF-κB signaling pathways in macrophages [ 38 ], alveolar bone resorption may occur in vivo through the indirect action of IL-6 suppression because of its anti-inflammatory effect and its direct effects on BMMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, through inhibition of NF‐κB, GAL exerts significant anti‐inflammatory effects in different models such as osteoclastogenesis (Huh et al, 2013; X. Li et al, 2021), cardiometabolic disorders (Prasatthong et al, 2021), vascular remodelling (Chaihongsa et al, 2021), renal inflammation (H. Lu et al, 2019), rheumatoid arthritis (RA) (Fu et al, 2018), and psoriasis‐like skin inflammation (Sangaraju et al, 2021).…”
Section: Inflammatory Sensitive Signals and Gal's Regulationmentioning
confidence: 99%
“…In human osteoarthritis chondrocytes, GAL increased ECM synthesis and decreased ECM degradation, and the intra‐articular GAL injection slowed the progression of osteoarthritis in rat models (Lin et al, 2022). Through inhibition of MAPK and NF‐κB signaling pathways, Li et al (2021) reported that GAL is a promising therapeutic agent for osteoporosis. GAL decreased NFATc1, C‐Jun, and C‐Fos in addition to inhibition of ERK and p38MAPK phosphorylation.…”
Section: Anti‐inflammatory Effect Of Galmentioning
confidence: 99%
“…Galangin, a natural bioflavonoid extracted from a traditional Chinese herb, has a variety of biological activities, including antiinflammatory and antioxidant properties. (Li et al (2021a) showed that during the differentiation of bone marrow macrophages Frontiers in Pharmacology frontiersin.org studying osteoporosis, which has the characteristics of single modeling factor, great repeatability, high reliability of experimental results, and can successfully simulate postmenopausal osteoporosis in vivo. In vivo studies have shown that Vinp significantly reduces the number of osteoclasts and attenuates ovariectomy-induced bone loss.…”
Section: Natural Plant Derivatives and Compounds Modulate The Nf-κb A...mentioning
confidence: 99%
“…Galangin, a natural bioflavonoid extracted from a traditional Chinese herb, has a variety of biological activities, including anti-inflammatory and antioxidant properties. ( Li et al (2021a) showed that during the differentiation of bone marrow macrophages (BMMs) to OCs, galangin inhibited the phosphorylation of p38 and ERK in the MAPK signaling pathway, as well as downstream factors such as NFATc1, c-Jun and c-Fos. It also inhibits bone resorption by inhibiting lipopolysaccharide (LPS)-induced differentiation of OCs.…”
Section: Natural Plant Derivatives and Natural Compoundsmentioning
confidence: 99%